Efficacy of praziquantel treatment of schistosomiasis in a non-endemic country: a follow-up of parasitological, clinical and immunological parameters - Giboda, M; Loudová, J; Shonová, O; Boucková, E; Horácek, J; Numrich, P; Ruppel, A; Vítovec, J; Lukes, S; Noll, P (Journal of hygiene, epidemiology, microbiology, and immunology, 1992)
Schistosomiasis patients were immigrants to Czechoslovakia from Angola and Yemen. Most of them had light or moderate infections and felt subjectively healthy. They received treatment with praziquantel (two doses with a total of 40 mg/kg) and were followed up for several years. In nine of 13 patients, Schistosoma haematobium or S. mansoni eggs with undamaged miracidia were detected in biopsies from the bladder or the rectum one year or later after treatment. Granulomatous reactions in the rectum and bladder lesions of stage 1 including thickened bladder walls persisted in most of the patients. Antibody levels against adult S. mansoni worm antigen remained elevated for at least two years after therapy in some patients and declined in others. Among the nine patients, for whom pre- and post-treatment sera were available, the changes in relative levels of antibodies did not strictly correlate with the continued presence of schistosome eggs in, or their absence from, biopsies. We discuss the results obtained with sensitive diagnostic techniques in the absence of subjectively perceived disease.
Keywords: protilátky helmintové; Praziquantel; Treatment Outcome; zvířata; schistosomiasis mansoni; Antibodies, Helminth; Animals; lidé; Adult; dospělí; praziquantel; schistosomiasis haematobia; Schistosoma mansoni; Schistosoma haematobium; výsledek terapie; Cohort Studies; kohortové studie; kolon; Male; feces; nemoci močového měchýře; Colon; Schistosomiasis haematobia; Humans; mužské pohlaví; Schistosomiasis mansoni; Urinary Bladder Diseases; Feces